Interferencia morfosintáctica del quechua al castellano en la provincia del Cusco - Condori Pauccara, José (2024)
The Spanish spoken in the province of Cusco belongs to Andean Spanish, this because of the linguistic contact between Quechua and Spanish. This linguistic relationship generates various linguistic cases such as bilingualism, interference, substitution of one language for another, etc. The objective of this investigation is to describe and analyze the morphosyntactic interference from Quechua into Spanish spoken by bilinguals in the province of Cusco. The methodology used the qualitative approach and, consequently, the descriptive explanatory method. The linguistic corpus is made up of the information noted in the linguistic record sheet and the series of recordings of the interview. Also, the techniques that were used were observation andthe interview.The instruments used were the linguistic record sheet and a semi-structured questionnaire for the interview. The study design is of a non-experimental, cross-sectional nature. The results obtained show that morphosyntactic interference from Quechua to Spanish is manifested in linguistic insertion, omissions, grammatical substitutions, grammatical discordance, and solecism. Finally, the linguistic cases analyzed are natural expressions of the bilingual, without taking into account whether the bilingual is a native or non-native speaker.